Goals/ages of the childhood times: small children, age relationships, and Preschool Education - Patricia Dias Prado (Universidade Estadual Paulista Júlio de Mesquita Filho, 2012)
This article aims to divulge the results of a completed Ph.D research, that investigated, through ethnographic study, the age relationships between small children (from 3 to 6 years) at a public Preschool Education institution in the state of Sao Paulo, Brazil. Expanding the concept of childhood beyond an age scope, within the field of Social Sciences, particularly Anthropology, articulated to the Brazilian and Italian productions in the field of Preschool Education, children show to be not just reproducers of determinations according to steps and timelines imposed, but they are also inventors of new ways of being a certain age, questioning the goals of the childhood ages and proposing the construction of an anti-age and inter-age groups pedagogy.